2022
DOI: 10.3389/fonc.2022.959630
|View full text |Cite
|
Sign up to set email alerts
|

Case report: MicroRNA-10b as a therapeutic target in feline metastatic mammary carcinoma and its implications for human clinical trials

Abstract: Ninety percent of deaths from cancer are caused by metastasis. miRNAs are critical players in biological processes such as proliferation, metastasis, apoptosis, and self-renewal. We and others have previously demonstrated that miRNA-10b promotes metastatic cell migration and invasion. Importantly, we also showed that miR-10b is a critical driver of metastatic cell viability and proliferation. To treat established metastases by inhibiting miR-10b, we utilized a therapeutic, termed MN-anti-miR10b, composed of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In patients with BC stages I, II, and III, miR-1290 expression was higher than in stage IV patients, which is evidence of it being a potential biomarker for early BC detection [120]. Savan et al [121] showed that miRNA-10b promotes metastatic cell invasion and migration. This study shows that anti-miR10b can inhibit the miR-10b target without toxicity [121].…”
Section: Micrornasmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with BC stages I, II, and III, miR-1290 expression was higher than in stage IV patients, which is evidence of it being a potential biomarker for early BC detection [120]. Savan et al [121] showed that miRNA-10b promotes metastatic cell invasion and migration. This study shows that anti-miR10b can inhibit the miR-10b target without toxicity [121].…”
Section: Micrornasmentioning
confidence: 99%
“…Savan et al [121] showed that miRNA-10b promotes metastatic cell invasion and migration. This study shows that anti-miR10b can inhibit the miR-10b target without toxicity [121]. MiR-148a expression was associated with unfavorable clinical parameters and lower survival in BC patients and according to Li et al (2020), MiR-148a plays an oncogenic or tumor suppressor role in different cancer types [122].…”
Section: Micrornasmentioning
confidence: 99%
“…By controlling HOXD10, E-cadherin, and syndecan-1, miRNA-10b significantly increases tumor cell invasion and metastasis in the setting of BC [ 11 , 12 ]. Invasion and migration are facilitated by miRNA-10b, an important factor in the metastatic phase of breast cancer [ 13 ]. miR-10b has been described as an oncogenic miRNA that is overexpressed in different types of cancer and is implicated in tumor invasion and metastasis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are regarded as small noncoding RNAs of 20-24 nucleotides that negatively modulate gene expression by directly binding to the 3'-untranslated region (UTR) of target mRNA (3). MiRNAs play vital roles in many physiologic processes, including cell proliferation, differentiation, apoptosis, and self-renewal (4). Aberrant miRNAs are widely involved in cancer biologies, such as tumorigenesis, tumor growth, invasion, metastasis, and angiogenesis (5), and recently, several cancer-associated miRNAs were reported to function as biomarkers to predict the prognosis and treatment response of patients with AML (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%